Determination of the proton RBE in the rat spinal cord: Is there an increase towards the end of the spread-out Bragg peak?. Issue 1 (July 2018) - Saager, Maria; Peschke, Peter; Brons, Stephan; Debus, Jürgen; Karger, Christian P.
Abstract: Background and purpose: To determine the relative biological effectiveness (RBE) of protons in the rat spinal cord as a function of linear energy transfer (LET) and dose. Materials and methods: The rat cervical spinal cord was irradiated with single or two equal fractions (split doses) of protons at four positions (LET 1.4–5.5 keV/µm) along a 6 cm spread-out Bragg peak (SOBP). From dose-response analysis, TD50 - (dose at 50% effect probability) and RBE-values were derived using the endpoint of radiation-induced myelopathy. Results: Along the SOBP, the TD50 -values decreased from 21.7 ± 0.3 Gy to 19.5 ± 0.5 Gy for single and from 32.3 ± 0.3 Gy to 27.9 ± 0.5 Gy for split doses. The corresponding RBE-values increased from 1.13 ± 0.04 to 1.26 ± 0.05 (single doses) and from 1.06 ± 0.02 to 1.23 ± 0.03 (split doses). Conclusions: For the relative high fractional doses, the experimental RBE at the distal edge of the proton SOBP is moderately increased. The conventionally applied RBE of 1.1 appears to be valid for the mid-SOBP region, but the higher values occurring more distally could be of clinical significance, especially if critical structures are located in this area. Further in vivo studies at lower fractional doses are urgently required.